Removal of arsenite and arsenate using hydrous ferric oxide incorporated into naturally occurring porous diatomite - Jang, M.; Min, S.H.; Kim, T.H.; Park, J.K. (2006)
In this study, a simplified and effective method was tried to immobilize iron oxide onto a naturally occurring porous diatomite. Experimental results for several physicochemical properties and arsenic edges revealed that iron oxide incorporated into diatomite was amorphous hydrous ferric oxide (HFO). Sorption trends of Fe (25%)-diatomite for both arsenite and arsenate were similar to those of HFO, reported by Dixit and Hering (Environ. Sci. Technol. 2003, 37, 4182-4189). The pH at which arsenite and arsenate are equally sorbed was 7.5, which corresponds to the value reported for HFO. Judging from the number of moles of iron incorporated into diatomite, the arsenic sorption capacities of Fe (25%)-diatomite were comparable to or higher than those of the reference HFO. Furthermore, the surface complexation modeling showed that the constants of ≡SHAsO4- or ≡SAsO42- species for Fe (25%)-diatomite were larger than those reference values for HFO or goethite. Larger differences in constants of arsenate surface species might be attributed to aluminum hydroxyl (≡AI-OH) groups that can work better for arsenate removal. The pH-controlled differential column batch reactor (DCBR) and small-scale column tests demonstrated that Fe (25%)-diatomite had high sorption speeds and high sorption capacities compared to those of a conventional sorbent (AAFS-50) that is known to be the first preference for arsenic removal performance in Bangladesh. These results could be explained by the factthat Fe (25%)-diatomite contained well-dispersed HFO having a great affinity for arsenic species and well-developed macropores as shown by scanning electron microscopy (SEM) and pore size distribution (PSD) analyses. © 2006 American Chemical Society.